Veřejná volba v České republice - Bartošová, Martina (Univerzita Pardubice, 2006)
Diplomová práce přináší shrnutí teorie veřejné volby. Je popsána volební procedura v České republice ve vztahu k příslušným legislativním předpisům, používané metody pro přepočet hlasů v ČR, úloha Českého statistického úřadu při volbách. Jsou systematizovány výsledky voleb do Poslanecké sněmovny Parlamentu ČR, do Senátu Parlamentu ČR a do Zastupitelstev statutárních měst Pardubice a Hradec Králové. Výsledky jsou analyzovány. Je sledován vliv vybraných makroekonomických veličin na zisky hlasů jednotlivých politických stran. Proporcionalita výsledků voleb je hodnocena s využitím indexu odchýlení od proporcionality.

Public choice is a process which couples individual preferences into collective decisions. It is the aggregation of big amount of votes into one decision. This thesis offers the summary of public choice theory. The electoral procedures in the Czech Republic in relation to corresponding legal enactments, the methods of votes conversion used in the Czech Republic and the role of the Czech Statistical Office during elections are described. The election returns for the Chamber of Deputies and the Senate of the Parliament of the Czech Republic, for Municipal corporations of corporate towns Pardubice and Hradec Králové are systematized. The results are analysed. The influence of selected macro-economic variables on vote gains of particular political parties is examined. The election returns proportionality is evaluated by the index of deviation from proportionality.
Public choice in the Czech republic
Keywords: elections; electoral system; voters; votes; seats; volby; volební systém; voliči; hlasy; mandáty